PENGEMBANGAN MODUL BERBASIS PROBLEM SOLVING PADA MATA PELAJARAN KIMIA SMA POKOK BAHASAN KOLOID - Izzati Sadrina; Erviyenni '; Herdini ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this research was develop module based on problem solving in colloid of chemistry in senior high school subject in terms of valid based on the content properness, serve, language, and graphic. The type of this research was research and development (R&D) with development process of 4-D model which include Define, Design, Develop, and Disseminate. This research was to develop phase. The object of this research was the module based on problem solving. The data analysis technique used for this research done by calculated the percentage of validation value. Instrument of data collection was validation sheet given by three validators. The average score of valuation to four expediency aspect by validator’s team such us content properness, serve, language, and graphic has expediency value continued 92,78%, 93,75%, 98,33%, and 97,50%. Thus, the average score tatality of module based on problem solving in colloid subject is 95,59% which is in valid criteria. Based on results of data analysis can be concluded that module based on problem solving has been valid and can be used in colloid of chemistry in senior high school subject.Key Words: Module, Problem Solving, and Colloid.